2013
DOI: 10.4172/2155-9600.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Nutritive Properties of Bitter Kola (Garcinia Kola)

Abstract: This study evaluated the proximate composition, nutritive properties and phytochemical content of Bitter Kola. Colour, shape, texture, odour, flavour and colour of peeled seed were some of the physical properties observed. Carbohydrate (70.31%) was observed to be the most abundant biological molecule. The moisture content (9.28%) was significantly high (P<0.05) while Ash (4.17%), crude fiber (3.94%) ether extract/fat (1.03%) and crude protein (11.27%) were present in appreciable amounts. Vitamins A, C, E, B1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…G. gummi-gutta pericarp had a high amount of oil compared to G. indica and G. xanthochymus pericarp. Similar results were reported by Mazi et al [37] in Garcinia kola. Since the pericarp was sticky to handle, wax content was estimated which indicated that the pericarp contains 0.2-1.1 % of wax.…”
Section: Fruit Compositionsupporting
confidence: 92%
“…G. gummi-gutta pericarp had a high amount of oil compared to G. indica and G. xanthochymus pericarp. Similar results were reported by Mazi et al [37] in Garcinia kola. Since the pericarp was sticky to handle, wax content was estimated which indicated that the pericarp contains 0.2-1.1 % of wax.…”
Section: Fruit Compositionsupporting
confidence: 92%
“…Previous studies revealed that G. kola seed powder supplemented in animal diets also promoted growth and feed conversion efficiency in Clarias gariepinus juveniles (Adeniji et al 2018) and Oreochromis niloticus adults (Sulem-Yong et al 2018). The proximate and phytochemicals analysis of G. kola seeds revealed that it is rich in nutrients such as, vitamins, minerals, phytochemicals but low in anti-nutrients content, indicating that it could be used as supplements in feed manufacturing (Adesuyi et al 2012;Mazi et al 2013;Onyekwelu et al 2015). According to Onyekwelu et al (2015), the low antinutrients content in G. kola indicates that its consumption would not pose nutritional or health problems.…”
Section: Discussionmentioning
confidence: 99%
“…The plant extracts are used in the treatment of laryngitis, cough and liver diseases [3]. The phytochemical study of the Garcinia kola seed highlighted the presence of flavonoids, alkaloids, sterols, phenols and tannic acids [4].…”
Section: Introductionmentioning
confidence: 99%